Prototipe CRITTING BADOT (Car Security System Monitoring Based on STNK) - Nasruloh, Agan; Kurniawan, Deny; Subekti, Massus (LPPM Universitas Negeri Jakarta, 2017)
The crime of burglary vehicle accompanied also by forgery vehicle registration certificate of vehicle number.For it, needed CRITING BADOT (Car Security System Monitoring Based On Stnk), an apparatus capable of preventing motor vehicle theft by means of technology RFID and SMS Gateway, blends the ignition and vehicle registration into a single entity, change the key of the car being contact id card, capable of being on the monitoring of the position the car.This tool requires the driver to be always bring vehicle registration wherever, because the vehicle registration was also serves as the ignition.The prototype CRITTING BADOT use RFID, Arduino Mega 2560 , 4x4 Keypad, GPS module, GSM module coupled be a system of that runs well.RFID used to read id of vehicle registration to turn a valve gasoline and keypad serves to enter password as well as turn the stater relay.When the existence of acts of theft with breaking into the door, then with the same time GPS going to read the position of the car and send data in the form of the point GPS coordinates using SMS Gateway to the cell phone number owners who have determined.This system having the difference reading GPS with google maps an average of 3,678 meters and reading tag RFID maximum 4,5 cm. Kejahatan pencurian kendaraan disertai juga dengan pemalsuan STNK (Surat Tanda Nomor Kendaraan). Untuk itu, dibutuhkanlah CRITING BADOT (Car Security System Monitoring Based on STNK), suatu alat yang mampu mencegah pencurian kendaraan bermotor dengan menggunakan teknologi RFID dan SMS Gateway, mengefisiensikan kunci kontak dan STNK menjadi satu kesatuan, mengubah kunci kontak mobil menjadi ID Card, mampu memonitoring posisi mobil. Alat ini mengharuskan pengemudi agar selalu membawa STNK kemana pun, karena STNK tersebut juga berfungsi sebagai kunci kontak. Prototipe CRITTING BADOT menggunakan RFID, Arduino Mega 2560, Keypad 4x4. Modul GPS, Modul GSM yang dipadukan menjadi sistem yang berjalan dengan baik. RFID berfungsi membaca ID dari STNK untuk mengaktifkan katup bensin dan keypad berfungsi untuk memasukkan password serta mengaktifkan relay stater. Ketika adanya tindak pencurian dengan membobol pintu, maka dengan waktu bersamaan GPS akan membaca posisi mobil dan mengirim data GPS berupa titik koordinat menggunakan SMS Gateway kepada nomor ponsel pemilik yang telah ditentukan. Sistem ini memiliki selisih pembacaan GPS dengan google maps rata-rata sebesar 3,678 Meter dan pembacaan tag RFID maksimal 4,5 CM.